Evaluation of the sensitivity profile of Escherichia coli isolated from urinary tract infection to antimicrobials - Cruz, Luisa Ferreira da (2021)
The most commonly isolated etiologic agent of urinary tract infections (UTIs) is the bacterium Escherichia coli (E. coli), which accounts for about 40% of cases. As Gram-negative microorganisms, E. coli have a complex cell wall, which is why some antibiotics are less effective when compared to their action against Gram-positive bacteria. Therefore, the objective of this work is to evaluate the sensitivity profile of clinical samples of E. coli bacteria to antimicrobials used in the treatment of UTI through the agar diffusion test. After data collection and analysis, it was possible to observe that most clinical isolates were resistant to amoxicillin and were more sensitive to nitrofurantoin and chloramphenicol. From the information obtained after analyzing the data, it was possible to observe that despite the strict control of the administration of antimicrobial drugs, the incidence of resistant bacteria to such drugs is alarming.